The value of nursing care in the paradigm of chronicity and dependency. New roles and redesigns - Ferrer-Arnedo, Carmen; Santamaría-García, José María; Fernández-Batalla, Marta; Salazar-Guerra, Rosa (Investigación y Educación en Enfermería, 2014)
The future of Healthcare Systems not only faces financial troubles, but also – perhaps worse, the need to redesign its service offers. It is necessary to work for all the knowledge available to be placed at the service of patients and society, generating much more efficient services and opening to a redesign where nurses lead in new services supported on the strategy of effective care. Additionally, it is hoped that patients assume a responsibility and nurses another: that of accompanying patients during their disease process to become for them a support in their self-care efforts. The new role that must be assumed by community nurses is that of becoming the coaches of chronic patients and of their caregivers so they can reach a situation of equilibrium, between their desires and what they must do, to, thus, assume their responsibility in the selfprovision of Basic Care. How to cite this article: Ferrer-Arnedo C, Santamaría-García JM, Fernández-Batalla M, Salazar-Guerra. The value of nursing care in the paradigm of chronicity and dependency. New roles and redesigns. Invest Educ Enferm. 2014; 32(3):